Hubungan Kekerasan dalam Rumah Tangga dengan Tingkat Kecemasan pada Wanita - Carla Marchira, Yosie Amylia, Mariyono Sedyo Winarso (Berita Kedokteran Masyarakat (BKM), 2007)
Background: Incidence of domestic violence in DIY and Central Jawa increases every year. The women as a victim of violence have a big risk to suffered from some serious health problem, mental illness at the most. A poor marital relationship caused by domestic violence could be a social stressor and current vulnerability factors in anxiety.Objectives: The study aims at identifying the types of domestic violence, the degree of anxiety, and also the correlation between domestic violence and  anxiety among women  who have consultation in Rifka Annisa Women’s Crisis Center Yogyakarta.Methods: This study was a descriptive analytic correlation study using cross sectional design. The subject of this study were 30 women  who have consultation in Rifka Annisa Women’s Crisis Center Yogyakarta and taken by purposive sampling technique. The data was collected by means of TMAS questionnaires. Data analysis on the correlation between domestic violence and anxiety was done by using Chi Square statistic test.Results: Findings from this study showed that 43,3% subject being physically and emotionally assaulted. Most subject were experiencing moderate level of anxiety (53,3%). Chi Square test showed that there was significant difference between domestic violence and anxiety among women  who have consultation in Rifka Annisa Women’s Crisis Center Yogyakarta (X2=18.307, df=10, P<0.05).Conclusion: Most of the women  who have consultation in Rifka Annisa Women’s Crisis Center Yogyakarta had experienced more than two types of violence (80%) and 53,3% respondents report moderate level of anxiety. There are significant difference between domestic violence and anxiety among women who have consultation in Rifka Annisa Women’s Crisis Center Yogyakarta.Keywords: domestic violence, anxiety, women